Новый способ аналогового моделирования кинематики процесса осадки - Добров, И. В.; Семичев, А. В.; Новиков, Б. О.; Гетьман, Е. В. (НТУ "ХПИ", 2014)
Разработан метод аналогового моделирования кинематики процесса осадки симметричной заготовки плоским пуансоном с использованием пружины сжатия в условиях ее упруго-пластической деформации. Установлена взаимосвязь характера изменения скорости деформации заготовки при осадке с изменением шага витков пружины при ее динамическом нагружении. С использованием современных средств цифровой киносъемки и персональных компьютеров при анализе деформации витков пружины сжатия установлен характер изменения скорости деформации элементов заготовки по ее высоте. Полученные расчетные значения величин скоростей деформации заготовки качественно соответствуют результатам натурного эксперимента при осадке цилиндрической заготовки в производственных условиях

It is developed analog modeling of kinematics of process of forging of symmetric stock with flat dies using of compression spring at elastic and plastic deformation. It is based on the equations for describing of forming of stock in elastic and plastic zones of deformation which are the same. It is researched low of velocity of deformation of stock at forging depending on path of spring at dynamic loading. It is determined nature of deformation velocity of stock at forging at static and dynamic loading with change of path of spring. Low of deformation of active coils of compression spring depending on height is researched using of modern digital filming and personal computer. Computed values of velocities of deformation of stock are consistent with the results of experiment at forging of cylindrical stock in industrial conditions. Liner low of deformation can not be reached at processes of working of metals by pressure. Velocities of deformation of active coils of compression spring are different at forging at direction of force. The friction forces restrict forming of stock at forging
New method of analog modeling of kinematics of forging
Keywords: обработка металлов давлением; пружина сжатия; упругая деформация; пластическая деформация; скорость деформации; analog modeling; forging; compression spring; elastic; plastic deformation; deformation velocity